THE ROLE OF GEOINFORMATION TECHNOLOGIES IN IMPROVING THE DESIGN OF MEDICAL INSTITUTIONS' ACTIVITIES WITHIN THE ELECTRONIC GOVERNMENT MANAGEMENT SYSTEM - Ibroxim Xabibullayev; Faxriddin O‘rinboy o‘g‘li Axrorov; Ismat Qudratillaevich Telyaev (Web of Journals Publishing, 2025)
The article highlights the necessity of using a geoinformation system in the design of organizing the activities of medical institutions within the electronic government management system, as well as its capabilities and effectiveness.
Keywords: E-government, healthcare, system, project, management, planning, automation, geoinformation system, activity, service delivery, region, capability, efficiency.